Regional network (centrality) and Covid-19 spread in West Kalimantan - Muazir, S; Lestari, Lestari; Alhamdani, M R; Nurhamsyah, M (ASCEE, 2022)
At the end of 2019, the disease was identified in the Wuhan region China as coronavirus 2019 or Coronavirus Disease (Covid-19). This disease quickly spread to other nations, including Indonesia and West Kalimantan. The alert for the Covid-19 outbreak in West Kalimantan began with the release of the Covid-19 emergency response circular letter by the Governor of Kalbar. The spread of infectious diseases can occur because of the “connectivity” between areas. This paper is intended to describe the interaction between cities/ regencies in West Kalimantan and the relation to the spread of the Covid-19 pandemic. This paper used centrality measurement (network analysis) as a primary method. Afterward, it will then be superimposed with the Covid-19 spread data, which results in several trends in the position of each regency. From findings, cities/ regencies with high centrality scores tend to have a high number of confirmed cases (positive) of Covid-19.